Question Find the general solution for $$xy' - y = -x .e^{\frac{y}{x}}$$

My attempt:

The only two methods I have learnt in regards to solving First order ODE's are using an integrating factor and separation of variables. I tried to go with the first method and got:

$$y' - \frac{1}{x}y= -e^\frac{y}{x}$$

But I cannot advance from here as there is a y term in the exponential.

  • 1
    $\begingroup$ set $w=\frac{y}{x}$ and calculate $w'$ $\endgroup$
    – polfosol
    Oct 3 '16 at 11:44
  • $\begingroup$ $e^{-w}dw=-\frac{dx}{x}$ and so on $\endgroup$
    – polfosol
    Oct 3 '16 at 11:48

Let $y(x)=xr(x)$ which gives $y'(x)=r(x)+xr'(x)$:

$$xy'(x)-y(x)=-xe^{\frac{y(x)}{x}}\Longleftrightarrow x\left(r(x)+xr'(x)\right)-xr(x)=-xe^{\frac{xr(x)}{x}}\Longleftrightarrow\frac{r'(x)}{e^{r(x)}}=-\frac{1}{x}$$

Now, integrate with respect to $x$:


And use:

  1. Substitute $u=r(x)$ and $\text{d}u=r'(x)\space\text{d}x$: $$\int\frac{r'(x)}{e^{r(x)}}\space\text{d}x=\int\frac{1}{e^u}\space\text{d}u=\int e^{-u}\space\text{d}u=-\frac{1}{e^u}+\text{C}=\text{C}-\frac{1}{e^{r(x)}}$$
  2. $$\int-\frac{1}{x}\space\text{d}x=-\int\frac{1}{x}\space\text{d}x=\text{C}-\ln\left|x\right|$$

So, we get (set $r(x)=\frac{y(x)}{x}$ back):

$$-\frac{1}{e^{\frac{y(x)}{x}}}=\text{C}-\ln\left|x\right|\Longleftrightarrow e^{\frac{y(x)}{x}}=\frac{1}{\ln\left|x\right|+\text{C}}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.